A dual-end-pumped Ho:YAG laser with a high energy output. (31st August 2015) - Duan, X M; Cui, Zh; Li, L J; Dai, T Y; Yu, K K; Yao, B Q
Abstract We report a high energy output from a Ho:YAG oscillator resonantly double-end pumped by Tm:YLF lasers at room temperature. The maximum pulse energy of 52.5 mJ was achieved at a pulse repetition rate of 100Hz and a pulse duration of 35.2 ns, corresponding to a peak power of approximately 1.5 MW. The output wavelength was 2090.7 nm with beam quality factor M2 ∼ 1.2.